The optimal course and frequency of Tai Chi for knee osteoarthritis: a systematic review and meta-analysis of randomized controlled trials - Deng, Jing; Zhang, Leyi; Chen, Fengjiao; Tao, Yufeng; Yang, Hao; Yu, Lanlan; Zhang, Chi (Frontiers in Public Health, 2025)
ObjectivesKnee osteoarthritis (KOA) is a highly prevalent degenerative joint disease worldwide and an important cause of disability. Currently, medication and surgical interventions are commonly used in clinical practice, but there are limitations such as significant side effects and high medical costs. Tai Chi, as a non-pharmacologic intervention, is recommended for its safety and few adverse effects. However, there is still a lack of consensus on the optimal course and frequency of Tai Chi intervention, and there is an urgent need to optimize clinical intervention protocols. In order to scientifically assess the optimal course and frequency of Tai Chi for the treatment of KOA, this study integrates the existing evidence through a systematic review and meta-analysis, and aims to provide standardized protocols for Tai Chi training in clinical practice.MethodsPubMed, Embase, Cochrane Library, Web of Science, Scopus, EBSCO, CNKI, Wanfang Database, and VIP database were searched from establishment to August 30, 2025. Two reviewers independently extracted data and assessed the quality of the literature and the certainty of the evidence for each outcome according to the Cochrane Risk of Bias Tool and the Grading of Recommendations, Assessment, Development & Evaluation (GRADE) approach. Outcome measures included Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain, WOMAC stiffness, WOMAC physical function, Visual Analogue Scale (VAS) pain, 36-item Short Form Health Survey (SF-36) Physical Component Summary (PCS), and SF-36 Mental Component Summary (MCS). For combined outcomes, standardized mean difference (SMD) and 95% confidence interval (CI) were calculated. Review Manager 5.4.1, Stata 15.0 and GRADE profiler software were used to statistically analyze and plot the included information.ResultsA total of 13 randomized controlled trial (RCT) studies (n = 701) were included in this review. The results of the meta-analysis showed that Tai Chi relieved pain (WOMAC pain: SMD = −0.41, 95%CI [−0.58, −0.25], p < 0.01; VAS pain: SMD = −0.33, 95% CI [−0.57, −0.10], p < 0.01), reduced stiffness (SMD = −0.27, 95% CI [−0.43, −0.11], p < 0.01), improved physical function (SMD = −0.52, 95% CI [−0.68, −0.36], p < 0.01), and improved physical health (SMD = 0.47, 95% CI [0.27, 0.67], p < 0.01). Subgroup analyses showed that the long-term (>16 weeks)/three-times-weekly Tai Chi training protocol was optimal (SMD = −0.74, 95% CI [−1.06, −0.41], p < 0.01; SMD = −0.96, 95% CI [−1.30, −0.63], p < 0.01) in terms of improvement of pain and physical function; and that in terms of improvement of stiffness, the short-term (≤16 weeks)/three-times-weekly Tai Chi training protocol was optimal (SMD = −0.52; 95% CI [−0.84, −0.19], p < 0.01); and in terms of improving physical functioning, a short-term (≤16 weeks)/twice-weekly Tai Chi training protocol was optimal (SMD = 0.44, 95% CI [0.21, 0.68], p < 0.01).ConclusionThis meta-analysis suggests that Tai Chi is effective in improving pain, stiffness, physical function, and physical health in patients with KOA. Patients with KOA should consider their specific conditions and choose a Tai Chi training protocol that suits their needs. The preliminary results of this meta-analysis indicate that for patients with pain and physical functional limitations, a long-term (>16 weeks)/three times weekly Tai Chi training regimen may be selected; for patients experiencing knee stiffness, a short-term (≤16 weeks)/three times weekly Tai Chi training regimen may be considered; and for KOA patients seeking to improve physical health through Tai Chi training, a short-term (≤16 weeks)/twice weekly Tai Chi training regimen may be selected. However, the number of large-sample studies in this review is limited, and more studies are urgently needed to confirm these results.Systematic review registrationIdentifier–CRD42024599921, https://www.crd.york.ac.uk/PROSPERO/myprospero.